The Interplay between Competitive Anxiety and Self-Confidence and Their Impact on the Accuracy of Performing Some Basic Football Skills among Female Students at Ashur University (The International Journal of Educational Sciences and Arts, 2026)
The current research aimed to identify the nature of the relationship and correlation between competitive anxiety, self-confidence, and the accuracy of performing (passing and dribbling) football skills among female students at Ashur University. The researcher used a descriptive correlational approach, as it was suitable for the nature of the study, on a sample of (30) female students from Ashur University, selected randomly. The researcher used the CSAI-2 scale to measure psychological variables and standardized skill tests to measure performance. The results showed a statistically significant inverse correlation between anxiety and skill performance, while self-confidence showed a strong positive correlation with performance accuracy ($P ≤ 0.05). The research concludes that emotional stability and enhanced self-confidence are fundamental pillars for developing motor learning and consolidating skills among beginner students.
Keywords: Self-Confidence; Situational Anxiety; Skill Tests; Motor Learning